INTERACTION EFFECT OF CHEMICAL AND ORGANIC FERTILIZERS ON THE YIELD AND YIELD COMPONENTS OF Gundelia rosea AT DIFFERENT PLANT DENSITIES IN THE FIELD - Vian D. A.,; F. H. Aziz, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Field experiments were conducted at two locations, Grdarasha Research Field Station, College of Agricultural Engineering Sciences, Salahaddin University – Erbil and Aquban special farm using randomized complete block design (RCBD) during two seasons 2019-2020 and 2020-2021 to study the effect of different plant densities and compost fertilizer of solid waste management and sorting of Akre district-Duhok province and NPK  (20:20:20) fertilizer on growth and edible portion characteristics of Gundelia rosea. The results indicated that the plants of the two years age in the both locations produce the highest value of length, dimeter, fresh and dry weight of edible portion with space increasing between plants and rows. While, total fresh and dry weight increased with decreasing the distance between plants and rows. Compost and compost + NPK fertilizer significantly increasing all edible portion parameters in both locations. The interaction between density and fertilizer resulted that D5 and compost and compost +NPK treatment produce the maximum rate of length, dimeter, fresh and dry weight of edible portion, while D1 and compost and compost + NPK record the highest total fresh and dry weight production.